Using the Simple View of Writing for Explaining English L2 Writing Variation. Issue 7 (27th October 2022) - Graham, Keith M.; Eslami, Zohreh
Abstract: This study examines the role of transcription and ideation, the dimensions in the Simple View of Writing, as predictors of narrative and expository writing of English language learners (ELLs). Data were collected from sixth-grade primary school ELL students ( N = 56) in Taiwan. Two writing samples, a narrative and an expository, were collected and scored using Curriculum-Based Measures of Writing (CBM-W). In addition, spelling, as a measure of transcription, and oral language, as a measure of ideation, scores were collected. The findings show that both spelling and oral language were found to be independent predictors of L2 writing. Spelling independently accounted for 36% of the variation in both narrative and expository writing, and oral language independently accounted for 24% and 35% of the variation in narrative and expository writing, respectively. When examined together in a regression model, spelling was found to be statistically significant for both narrative and expository writing whereas oral language was not. In light of the findings, the Simple View of Writing may be adequate as a theory for developing L2 writers, but further research is needed on the ideation dimension, both in its conceptualization for L2 writers and its role in the writing process.